'Choralbücher' from Northern Germany 'c'. 1800 – a Dataset for Studies in Hymnology, Music Culture and Figured Bass - Kirsten Gerhardt; Matthias Kirsch (Transactions of the International Society for Music Information Retrieval)
While the artistic hymns of J. S. Bach have often been the subject of digital analysis, the large corpus of Choralbücher with “everyday settings” still lacks this kind of acknowledgement. The similarities of these settings, however, allow assumptions about a “harmonic standard” of hymns. From the Reformation until around 1800, a core stock of around 100 hymn melodies had developed, which remained relatively stable in the repertoire for many decades thereafter, while their harmonized versions were always based on common contemporary procedures. In terms of compositional technique, hymn arrangements can therefore be seen as a genre that reacts to contemporary tonal differentiations and “records” them in a certain way. Analysing the similarities or differences in this large corpus is only possible by reading the data digitally. The dataset described in this article therefore includes four Choralbücher with “everyday settings,” that were transcribed with a focus on digital processing, especially on a digital analysis of the figured bass. All four books are Choralbücher of the Duchies of Schleswig and Holstein, published between 1755 and 1832. The transcriptions and a few sample queries can be found on GitHub: Transcriptions: https://github.com/Chorale-Corpus. Queries: https://github.com/cau-mi/musicau-demo.